2019
DOI: 10.1021/acsami.9b04386
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Vacancy-Tunable Electrochemical Properties of Electrodeposited Molybdenum Oxide Films

Abstract: Molybdenum oxides have been widely studied in recent years, owing to their electrochromic properties, electrocatalytic activities for hydrogen evolution reactions (HERs) and excellent energy storage performance. These characteristics strongly depend on the valence states of Mo in the oxides such as IV, V, and VI, which can be efficiently altered through oxygen deficiencies within the oxides. Here, we present a colloidal electrodeposition method to introduce oxygen vacancies in such Mo oxide films. We prepared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 97 publications
(51 citation statements)
references
References 49 publications
3
48
0
Order By: Relevance
“…To analyze the phase composition of the as-synthesized vanadium oxide nanoparticles, the colloidal suspension was dried at room temperature and characterized by the powder X-ray diffraction (XRD) measurement. The high-resolution TEM image, inset in Figure 1e, shows clear lattice fringes of 1.91 and 2.92 Å correspond to the and (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) planes, respectively. 00-028-1433) phase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To analyze the phase composition of the as-synthesized vanadium oxide nanoparticles, the colloidal suspension was dried at room temperature and characterized by the powder X-ray diffraction (XRD) measurement. The high-resolution TEM image, inset in Figure 1e, shows clear lattice fringes of 1.91 and 2.92 Å correspond to the and (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) planes, respectively. 00-028-1433) phase.…”
Section: Resultsmentioning
confidence: 99%
“…[6,7] The electrochromic battery exhibits self-coloration behaviors and eliminates the external voltage requirement for triggering the coloration process. [11][12][13][14][15] Among the TMOs, vanadium oxide is considered the most promising material for electrochromic displays because of its multicolor behaviors. [8][9][10] The lower charged/bleached potential indicates a lower energy consumption during the bleaching process.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, 2D α-MoO 3 nanosheets were fabricated and exhibited a considerable HER performance with low overpotential of 142 mV, to achieve 10 mA/cm 2 current density [61]. Zhang et al also found that MoO 3−y (valence state of V and VI) can be used for efficient electrocatalytic hydrogen evolution [62]. Second, the morphology is another key factor.…”
Section: Electrocatalytic Hydrogen Evolution Reactionsmentioning
confidence: 99%
“…During the deposition, electrical energy is supplied to provide a strong driving force for the redox reaction that ensures uniform growth and large surface area of TMO on the conductive substrate such as stainless steel, Ni foam, carbon cloth, ITO coated glass, etc. [53][54][55][56] Furthermore, it also features the advantage of doping TMO with other metals. [57] A conductive substrate as the working electrode is used and the deposition conditions, such as scan rate, number of cycles, electrolyte concentration, and pH, are used as controlling parameters to achieve high surface area and uniform deposition.…”
Section: Electrochemical Depositionmentioning
confidence: 99%